Reduced humoral response to two doses of COVID-19 vaccine in patients with inflammatory bowel disease: Data from ESCAPE-IBD, an IG-IBD study. Issue 2 (February 2023) - Macaluso, Fabio Salvatore; Principi, Mariabeatrice; Facciotti, Federica; Contaldo, Antonella; Todeschini, Alessia; Saibeni, Simone; Bezzio, Cristina; Castiglione, Fabiana; Nardone, Olga Maria; Spagnuolo, Rocco; Fantini, Massimo Claudio; Riguccio, Gaia; et al.
Abstract: Background: Patients on immunosuppressive drugs have been excluded from COVID-19 vaccines trials, creating concerns regarding their efficacy. Aims: To explore the humoral response to COVID-19 vaccines in patients with inflammatory bowel disease (IBD) Methods: E ffectiveness and S afety of C OVID-19 Va ccine in P atie nts with I nflammatory B owel D isease (IBD) Treated with Immunomodulatory or Biological Drugs (ESCAPE-IBD) is a prospective, multicentre study promoted by the Italian Group for the study of Inflammatory Bowel Disease. We present data on serological response eight weeks after the second dose of COVID-19 vaccination in IBD patients and healthy controls (HCs). Results: 1076 patients with IBD and 1126 HCs were analyzed. Seropositivity for anti-SARS-CoV-2 IgG was reported for most IBD patients, even if with a lesser rate compared with HCs (92.1% vs. 97.9%; p<0.001). HCs had higher antibody concentrations (median OD 8.72 [IQR 5.2-14-2]) compared to the whole cohort of IBD patients (median OD 1.54 [IQR 0.8-3.6]; p<0.001) and the subgroup of IBD patients (n=280) without any treatment or on aminosalicylates only (median OD 1.72 [IQR 1.0–4.1]; p<0.001). Conclusions: Although most IBD patients showed seropositivity after COVID-19 vaccines, the magnitude of the humoral response was significantly lower than in HCs. Differently from other studies, these findings seem to be mostly unrelated to the use of immune-modifying treatments (ClinicalTrials.govID:NCT04769258).